The protective role of glutamine against acute induced toxicity in rats. (May 2015) - Aydin, Mesut; Yildiz, Abdulkadir; Ibiloglu, Ibrahim; Ekinci, Aysun; Ulger, Burak Veli; Yuksel, Murat; Bilik, Mehmet Zihni; Ozaydogdu, Necdet; Ekinci, Cenap; Yazgan, Umit Can
Abstract Context: Deltamethrin (DLM) is an insecticide commonly used to protect agricultural crops against pests. QT prolongation with malignant ventricular arrhythmias are amongst the most common cardiovascular complications. DLM intoxication cause decreased level of antioxidant enzymes. Glutamine is the precursor of glutathione which is an antioxidant and has been demonstrated to improve outcome after several critical illnesses. Objective: We hypothesized that glutamine, by means of antioxidant characteristics, may antagonize the cardiotoxic effects of DLM. Materials and methods: All experiments were performed on 8-week-old male Wistar albino rats. The rats were divided into following groups (n = 10); Group I: control, Group II: l-glutamine, Group III: DLM, Group IV: DLM and after 4 h l-glutamine. Total antioxidant status (TAS), total oxidant status (TOS) and parameter analyses were performed in cardiac tissue. Results: We found that TAS was higher and TOS lower in DLM group. We also found that interstitial edema and inflammatory cell infiltration was significantly more frequent in DLM group and QT and QTc of DLM group were higher than others. Discussion: Recent studies have shown that several special amino acids, such as glutamine, glycine, arginine and taurine, exhibit cytoprotective effect on the cardiocyte, and have established the cardioprotective properties of glutamine. Conclusion: In this study, we showed the protective role of glutamine against cardiotoxic effects of DLM in rats. This protective effect was confirmed by showing both tissue level improvement in oxidative stress markers and improvement in prolonged QT interval.